Development and evaluation of time controlled release tablet of ketoprofen for the treatment of rheumatoid arthritis - Sharma, P H; Avari, J. G. (Journal of Applied Pharmaceutical Research, 2017)
The aim of present study was to develop and evaluate time controlled release tablet of Ketoprofen intended for rheumatoid arthritis. The cardinal sign of rheumatoid arthritis are stiffness, swelling and pain of one or more joints of the body characteristically most severe in the morning. Rheumatoid arthritis shows a significant circadian variation in its symptoms. Time controlled release tablet delivers the drug at definite time or in controlled rate. It consist of core tablet coated with two layers, the inner swelling layer and outer rupturable. Before compression of core tablet, drug- excipients compatibility study and precompression parameters were investigated. Core tablet was prepared by direct compression method. After evaluating core tablet for different evaluation parameter of tablet are coated with crosscarmellose sodium as inner swelling layer with different coating level. The prepared tablet again evaluated and coated with rupturable layer of ethylcellulose. The free film of ethylcellulose was evaluated for various parameters. The effect of microcrystalline cellulose and coating level of rupturable layer and swellable layer on lag time were investigated. The results shows as the amount of microcrystalline cellulose increase in core tablet the lag time decreases. The lag time increases with increase in coating level of swelling layer and rupturable layer. The water uptake study shows that higher ethylcellulose levels retards the water uptake and prolongs the lag time.